2004
DOI: 10.1007/s00216-004-2700-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the MRI contrast agent Gd-DTPA by SEC?ICP?MS

Abstract: The simultaneous determination of Gd(3+) and Gd-DTPA (DTPA: diethylenetriamino-pentaacetic acid), often used as contrast agent, is described. The proposed approach combines size-exclusion chromatography (SEC) and inductively coupled plasma-mass spectrometry (ICP-MS) for element-selective detection in order to determine also high-molecular Gd-complexes if present. This method was applied to the analysis of urine samples of a patient to whom Gd-DTPA was intravenously administered. The results showed that no conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…While RAPTA-T preferred binding to hTf over HSA, cisplatin was found to interact with both proteins to a similar extent. Similar investigations were also performed on gadolinium [ 29 , 30 ], titanium [ 31 ], and tungsten compounds [ 32 ], among others [ 3 ].…”
Section: Introductionmentioning
confidence: 79%
“…While RAPTA-T preferred binding to hTf over HSA, cisplatin was found to interact with both proteins to a similar extent. Similar investigations were also performed on gadolinium [ 29 , 30 ], titanium [ 31 ], and tungsten compounds [ 32 ], among others [ 3 ].…”
Section: Introductionmentioning
confidence: 79%
“…Although reversed phase chromatography (RP-HPLC) accounts for only very little retention for polar compounds, Mazzucotelli et al [132] separated one contrast agent and several degradation products using RP-HPLC/ICP-MS. Moreover, size exclusion chromatography (SEC) was used with ICP-MS to separate free Gd 3+ from Gd complexes and Gd adducts; however, the size differences between the individual Gd chelates are too small for effective SEC separation [133,134]. Ion chromatography (IC) [131,135], time-resolved luminescence (TRL) detector [136], and direct fluorescence [137] are also utilized for the separation of Gd species.…”
Section: Speciation Of Gd-casmentioning
confidence: 99%
“…Upon analyzing the urine from a patient to whom a linear contrast agent (Gd-DTPA) had been administered, it was found that Gd-DTPA was excreted almost completely (>99 %) within one day. When applying SEC/ICP-MS in this investigation it turned out that no free Gd 3+ was present when compared to Gd-DTPA in the analyzed urine samples [137]. A CE/ESI-MS method was used to perform further investigations of possible transmetallation products (such as Fe-DTPA, Cu-DTPA, Zn-DTPA, and free DTPA) of Gd-DTPA in human blood samples.…”
Section: Metal-based Diagnosticsmentioning
confidence: 99%